Exploring functions for the non-lemniscal auditory thalamus - Lee, Charles C. (Frontiers in Neural Circuits, 2015)
The functions of the medial geniculate body (MGB) in normal hearing still remain somewhat enigmatic, in part due to the relatively unexplored properties of the non-lemniscal MGB nuclei. Indeed, the canonical view of the thalamus as a simple relay for transmitting ascending information to the cortex belies a role in higher-order forebrain processes. However, recent anatomical and physiological findings now suggest important information and affective processing roles for the non-primary auditory thalamic nuclei. The non-lemniscal nuclei send and receive feedforward and feedback projections among a wide constellation of midbrain, cortical, and limbic-related sites, which support potential conduits for auditory information flow to higher auditory cortical areas, mediators for transitioning among arousal states, and synchronizers of activity across expansive cortical territories. Considered here is a perspective on the putative and unresolved functional roles of the non-lemniscal nuclei of the MGB.